Kinetics and Thermodynamics of Hg(II) Adsorption on Modified Vermiculite - An, Xiang-Jing; Qi, Yu; Li, Hong-Ling; Dan, Jian-Ming (Asian Journal of Chemistry, 2015)
This study investigated the processing of mercury-bearing wastewater using vermiculite expanded by microwave radiation and hydrogen peroxide and modified by chitosan. The adsorption properties of Hg(II) and the effects of pH, adsorption time and chitosan dosage were evaluated. At pH 6, the maximum removal rate was 96 % when 0.05 g/g chitosan was used for Hg(II) adsorption for 40 min. The kinetics and thermodynamics of Hg(II) adsorption on the modified vermiculite were also discussed. Under the optimum adsorption conditions, a pseudo-second-order kinetic model best described the reaction rate. Batch adsorption experiments conducted at different temperatures showed that the adsorption pattern followed the Freundlich isotherm model. The calculated thermodynamic parameters (DG, DH and DS) showed that the removal of Hg(II) using modified vermiculite was spontaneous and exothermic. These results proved the feasibility of using modified vermiculite to process mercury-bearing wastewater.